2015
DOI: 10.1111/iju.12727
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance monotherapy with gemcitabine after standard platinum‐based chemotherapy in patients with advanced urothelial cancer

Abstract: Objectives: To investigate the outcomes of gemcitabine maintenance monotherapy treatment for metastatic urothelial cancer. Methods: Gemcitabine maintenance monotherapy was used for metastatic urothelial cancer patients after standard platinum-based chemotherapy. A standard dose of 1000 mg/m 2 /month was given. If patients suffered adverse events or a noticeably compromised quality of life, treatment intervals were extended and doses lowered. Patients with metastatic urothelial cancer receiving only best suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 22 publications
0
33
4
Order By: Relevance
“…Seventy-nine percent of patients presented with stable disease, and 8% of the patients demonstrated disease regression after the main chemotherapy. Different from Muto et al [27] study and our study, presence of visceral metastasis was not identified as a prognostic factor in this study. In this regard, gemcitabine maintenance treatment after surgical treatment modality was used in two studies, which prolonged the survival.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Seventy-nine percent of patients presented with stable disease, and 8% of the patients demonstrated disease regression after the main chemotherapy. Different from Muto et al [27] study and our study, presence of visceral metastasis was not identified as a prognostic factor in this study. In this regard, gemcitabine maintenance treatment after surgical treatment modality was used in two studies, which prolonged the survival.…”
Section: Discussioncontrasting
confidence: 99%
“…The treatment break for patients who responded to first-line therapy is generally shortterm for about 2 to 3 months and it leads to rapid clinical progression and deterioration. [27] Moreover, clinical deterioration might not allow usage of second-line therapy in such patients. In this regard, chance of extended response and safe treatment with maintenance treatment should not be missed out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GEM monotherapy has been assessed in specific solid and haematological cancers (10)(11)(12) and, although no established maintenance therapy for UC is available at present, predominantly Japanese researchers have gained experience in this cancer entity with GEM monotherapy, demonstrating comparably low, although potentially promising response rates when used as a monotherapy alone, Following primary CBCC, a novel study published by Muto et al (7) demonstrated that GEM appeared to have a prognostic benefit in an UC patient collective (n=33) of palliative, non-surgically treated patients. The authors showed marked advantages in the maintenance group with respect to CSS and PFS rates compared with a control group receiving best supportive care alone, accompanied by a low rate of adverse events.…”
Section: Discussionmentioning
confidence: 99%